1986
DOI: 10.1159/000194904
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Respiratory Muscle Training in Patients with Neuromuscular Diseases and in Normals

Abstract: In order to evaluate the possible effects of respiratory muscle training in patients with neuromuscular disease, we trained a group of 12 patients and 6 normal subjects for 8 weeks with 4 weeks of strength training and 4 weeks of endurance training of the respiratory muscles. We measured static and dynamic lung volumes and maximal expiratory flows in a whole-body plethysmograph and endurance in an original set-up. The main finding was a significant rise in vital capacity and respiratory muscle endurance in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
3

Year Published

1991
1991
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 5 publications
0
24
0
3
Order By: Relevance
“…6,7 A simple and reliable test of VME is the longest time that a subject is able to voluntarily sustain 70% of the maximum breathing capacity or maximum voluntary ventilation (70%-MVV time). 8 This ventilatory intensity is close to the level of ventilation available for prolonged ventilation at maximal exercise in young healthy subjects. 9,10 To the best of our knowledge, no previous study has analyzed 70%-MVV time in SCI subjects with di erent levels of injury.…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…6,7 A simple and reliable test of VME is the longest time that a subject is able to voluntarily sustain 70% of the maximum breathing capacity or maximum voluntary ventilation (70%-MVV time). 8 This ventilatory intensity is close to the level of ventilation available for prolonged ventilation at maximal exercise in young healthy subjects. 9,10 To the best of our knowledge, no previous study has analyzed 70%-MVV time in SCI subjects with di erent levels of injury.…”
Section: Introductionmentioning
confidence: 55%
“…According to standard protocols of the American Thoracic Society, 1991 14 16 Ventilatory muscle endurance (70%-MVV time) Ten minutes after the MVV-12sec test, the ventilatory muscle endurance was measured as the highest time that the subject was able to voluntarily sustain a target ventilation corresponding to 70% of his MVV-12sec value (70%-MVV time). 8 Ventilation was measured breath-by-breath by electronic integration and summation of the signals by a¯ow-volume module of a computerized metabolic cart (Vista TurboFit, Vacumed, Ventura CA, USA). The actual ventilation was continuously displayed online in a video monitor of a host computer, while the target ventilation for each individual (70% of his MVV-12sec) was being identi®ed as a row to be followed.…”
Section: Methodsmentioning
confidence: 99%
“…Synthesising findings from the studies included is difficult due to their heterogeneity. Some have included adults only,363366 others both adults and paediatric subjects,367372 and some have included populations with different diseases or severities. Additionally the studies used different respiratory muscle training protocols—for example, duration of respiratory muscle training varied widely, from just 3–5 weeks364 to 2 years 372.…”
Section: Section 6 Neuromuscular Diseases and Musculoskeletal Disordementioning
confidence: 99%
“…ESTRUP et al [14] and recently WANKE et al [11] showed improvements in strength and endurance of the inspiratory muscles in patients with progressive muscular dystrophy. Only the latter was a controlled study.…”
Section: In Ns Sp Pi Ir Ra At To or Ry Y Mmentioning
confidence: 97%